An Exploratory Interview Study About Student Perceptions of Using Social Media to Facilitate Their Undergraduate Studies - Fuchs, Kevin (Frontiers in Education, 2022)
The true power of social media lies in its ability to enable users to connect and share information with anyone around the globe. The use of social media in education helps students get more useful information and connect with learning groups and other educational systems that make education convenient. The purpose of this exploratory interview study is to identify how undergraduate students use social media to support their studies. Moreover, the study examines student perceptions concerning the benefits and limitations of using social media for educational purposes. The empirical data for this study was generated through a series of semi-structured interviews with undergraduate students (n = 27) and analyzed thematically. Three themes emerged through the thematic analysis: (1) perceived usage of social media, (2) invasion of privacy, and (3) the approachable teacher. The results of the study offer practical implications for educators and policymakers about incorporating social media in their curricula.